Performance Evaluation of a Spray Dryer Based on Capacity and Yield using Biancaea sappan Extract - Bagas Satria Adjie Pratama; Samsudin Anis; Adhi Kusumastuti; Indra Nurul Hidayat; Deni Fajar Fitriyana (Universitas Negeri Semarang, 2026)
This study evaluates the performance of pressure nozzle type spray dryer. Maximum evaporation capacity was tested using water under various nozzle air pressures, airflow rates and at two inlet air temperatures. Solution of biancaea sappan extract mixed with maltodextrin were used to analyze powder yield, wall deposition, color of the powder, and efficiency of the spray dryer. An increase of nozzle air pressure and airflow rate gives finer atomization resulting in higher heat transfer. Combined with an increase in inlet air temperature, maximum evaporation capacity is achieved and can increase the powder yield of the spray dryer due to better moisture removal. Significant wall deposition was found in the head, drying chamber and cyclone duct. Visual analysis of the powder indicated that higher temperatures and prolonged residence time advanced the Maillard reaction, darkening the powder and could degrade its texture. A rather significant amount of powder loss was observed which is likely caused by fine particles leaving with exhaust air.